Efficacy of the Community Reinforcement and Family Training for concerned significant others of treatment-refusing individuals with alcohol dependence: A randomized controlled trial. (1st June 2016) - Bischof, Gallus; Iwen, Julia; Freyer-Adam, Jennis; Rumpf, Hans-Jürgen
Highlights: CRAFT effectively promotes treatment entry and improves mental health. CRAFT is effective outside the US treatment system. Sample recruitment and treatment motives influence effectiveness of CRAFT. Abstract: Background: The Community Reinforcement and Family Training (CRAFT) is a promising approach for Concerned Significant Others (CSOs) of alcohol-dependent individuals (ADI) that aims to engage treatment-refusing patients in alcohol treatment and to improve CSO functioning. To date, only two randomized controlled trials (RCTs) of CRAFT-based treatment for CSOs of ADI are available, both conducted in the U.S. For the first time, this study analyses the efficacy of CRAFT in a sample of CSOs outside of the U.S. Methods: Participants were recruited through the treatment system (general practitioners, psychotherapists, addiction counselling services) and through media solicitation. After brief screening, 94CSOs were randomly allocated to an immediate intervention condition (II) or a wait list condition (WL) that received the CRAFT intervention after 3 months. Data for the follow-up assessments at 3 and 6 months was provided by 78CSOs (II N = 42; WL N = 36). In addition, a follow-up assessment (f-u) was conducted after 12 months (Response rate 92%). Results: At 3-month f-u, II revealed significant higher ADI engagement rates (40.5%) compared to WL (13.9%); after WL received the CRAFT intervention, engagement rates did not differ between both groups at 6- and 12-month f-u. CSOs in both groups reported significant improvements in terms of mental health and family cohesion after having received the intervention, i.e. II at 3-months f-u and WL at 6-month f-u. Conclusions: Data show that CRAFT is effective for treating CSOs of alcohol dependent individuals in terms of treatment engagement and improvement of CSOs mental health and family cohesion.